2001
DOI: 10.1046/j.1532-5415.2001.49094.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Older Community‐Dwelling Adults Do Not Discuss Urinary Incontinence with Their Primary Care Physicians

Abstract: Embarrassment or lack of awareness of treatment options were not significant barriers to discussing UI. Adults with a fairly high frequency of UI (average of 1.7 episodes per day) did not view UI as abnormal or a serious medical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 15 publications
6
95
1
5
Order By: Relevance
“…The increasing prevalence rate in this study is primarily driven by an increase in big UI problems. A prior study consistently showed that patients tended to report UI‐related problems when symptoms became more severe 8. The prevalence estimate in this study is similar to that reported by Gnanadesigan et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increasing prevalence rate in this study is primarily driven by an increase in big UI problems. A prior study consistently showed that patients tended to report UI‐related problems when symptoms became more severe 8. The prevalence estimate in this study is similar to that reported by Gnanadesigan et al.…”
Section: Discussionsupporting
confidence: 89%
“…Even though UI can be managed by a number of treatment options 16, previous literature has demonstrated that older adults with UI considered it not as a medical condition but as a normal part of ageing 17. Because of this perception, they did not raise this health subject with their physicians and believed they could cope with UI 8.…”
Section: Discussionmentioning
confidence: 99%
“…UI is commonly concealed to preserve a women's sense of identity, and accepted as a normal part of ageing and being a woman (Bradway et al, 2010;Bush et al, 2001;Stewart, 2010). Frequently, elderly women lack knowledge of treatments that are available and are not often presented with opportunities to discuss or explain their UI with healthcare providers (Mardon et al, 2006;Zeznock et al, 2009;Dugan et al, 2001). Dugan et al (2001) reported that almost 70% of older adults experiencing UI were not asked by their healthcare provider about their UI.…”
Section: Empowering Women Experiencing Ui In Ltcmentioning
confidence: 99%
“…5,9,10 Studies on why women do not seek treatment for UI have identified potential reasons, such as embarrassment, viewing it as a normal part of aging, feeling that they can cope on their own, and having low expectations of benefit from treatment. 4,6,11,12 Very few studies, however, have addressed what women perceive as the cause of their leakage, 11,13 and none of these studies was conducted in the United States. This gap in incontinence research is crucial, as comprehending perceived causes is necessary to understanding care-seeking behavior and compliance with treatment recommendations.…”
mentioning
confidence: 99%